Learning a foreign language in the higher educational institution’s multicultural space - Svetlana V. Lapteva, Tatyana E. Shevnina., Tatyana I. Vorobyeva, Anatoly V. Kozlov, Olga S. Tamer, (Opción, 2019)
This research looks at the process of learning a foreign language in a multicultural space. A set of complementary research methods was used and a methodology was developed for teaching students a foreign language in a multicultural society. To achieve this goal, an experiment was carried out. In this experiment, 284 people participated on the basis of Tyumen Industrial University in Noyabrsk. As a result of the research, students appeared to be more tolerant and multicultural to their peers and to other cultures in general. Thus, the proposed teaching methodology can be effectively used in the educational program.